Pengaruh Pembelajaran Daring Di Masa Pandemi Covid-19 Terhadap Prestasi Belajar Matematika Siswa SMA - Azis Azis; Wa Ode Indah Murniati (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2022)
This study aims to determine the effect of the online learning during the Covid-19 pandemic on the Mathematics learning achievement of twelfth grade students of SMA Negeri 2 Kaledupa. This type of study was a quantitative research with ex post facto method, with a research population of 26 students in one class with 12th grade science students at SMA Negeri 2 Kaledupa. This study used the entire sample of class 12 with the number of students 26 students. The instruments were an online learning questionnaire and a form of documentation of even semester final exam results. The results of this data analysis through simple linear regression analysis, it was concluded that online learning during the Covid-19 pandemic had no impact on the mathematics learning achievement of 12th grade science students at SMA Negeri 2 Kaledupa. This could be seen in the calculated F value of 0.569 with a critical value of 0.574 > 0.05, this meant that H0 was accepted. In other words, there was no effect of the online learning process during the Covid-19 pandemic on the mathematics learning achievement of twelfth grade students of SMA Negeri 2 Kaledupa. Keywords: online learning, covid-19 pandemic, math learning achievement